2000
DOI: 10.1038/35006097
|View full text |Cite
|
Sign up to set email alerts
|

Control of TH2 polarization by the chemokine monocyte chemoattractant protein-1

Abstract: Activated T lymphocytes differentiate into effector cells tailored to meet disparate challenges to host integrity. For example, type 1 and type 2 helper (T(H)1 and T(H)2) cells secrete cytokines that enhance cell-mediated and humoral immunity, respectively. The chemokine monocyte chemoattractant protein-1 (MCP-1) can stimulate interleukin-4 production and its overexpression is associated with defects in cell-mediated immunity, indicating that it might be involved in T(H)2 polarization. Here we show that MCP-1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
543
5
8

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 776 publications
(579 citation statements)
references
References 28 publications
23
543
5
8
Order By: Relevance
“…Nonetheless, the preferential reduction of the levels of anti-AChR IgG2b suggested altered Th cell function. CCL2 plays a role in the development of both Th2 and Th1 cells [11,23]. In our model, IFN-c production by CD4 + T and CD8 + T cells in response to AChR stimulation was marginally impaired in CCL2 -/-mice ( Fig.…”
Section: Impaired Th17 Responses In Ccl2 -/-Micementioning
confidence: 70%
“…Nonetheless, the preferential reduction of the levels of anti-AChR IgG2b suggested altered Th cell function. CCL2 plays a role in the development of both Th2 and Th1 cells [11,23]. In our model, IFN-c production by CD4 + T and CD8 + T cells in response to AChR stimulation was marginally impaired in CCL2 -/-mice ( Fig.…”
Section: Impaired Th17 Responses In Ccl2 -/-Micementioning
confidence: 70%
“…In contrast to IL-10 production in response to septic peritonitis in vivo or Toll-like receptor engagement in vitro, lymph node cells from CCL2-deficient mice immunized with ovalbumin were impaired in their capacity to produce IL-10 following in vitro restimulation with antigen [42]. It should be considered, however, that under these experimental conditions IL-10 was produced by T lymphocytes, whereas in LPS-treated mice and mice subjected to septic peritonits IL-10 is predominantly released by macrophages.…”
Section: Discussionmentioning
confidence: 88%
“…Studies in CCL2/ MCP-1 -/-mice have indicated that this chemokine may be important for the induction and expression of polarized type 2 responses. Interestingly, data in CCR2 -/-mice have pointed to the opposite direction as far as polarized responses are concerned (33,62). In contrast, consistent results between gene targeting of the agonist and of the receptor have been obtained in terms, for instance, of susceptibility to atherosclerosis.…”
Section: Polarized Responsesmentioning
confidence: 99%
“…Some chemokines, including CCL2/MCP-1, induce IL-10 in macrophages. Moreover, data in knockout mice suggest that CCL2/ MCP-1 polarizes immunity in a type 2 direction (62). Chronic exposure to high chemokine concentrations in the tumor microenvironment may set in motion a chemokinecentered vicious circuit, leading to skewing towards a type 2 inflammatory response (77).…”
Section: Chemokines In Tumorsmentioning
confidence: 99%